The Next Buddha Will Be a Collective: Spiritual Expression in the Peer-to-Peer Era. - Bauwens, Michel (ReVision)
Religious and spiritual expression is always embedded in societal structures. If social structures are moving toward the form of distributed networks, what kind of evolution of spiritual expression can be expected? In this article, the author describes the general societal changes emerging and that he expects to become more prevalent in the future. He also examines to what degree these changes will affect individual and collective spiritual expression. The explanation of the peer-to-peer dynamic aids in understanding its application to spirituality. The author also discusses concrete examples of spiritual movements and initiatives that are specifically informed by peer-to-peer values and practices.